An Investigation of Yi Folk Song Knowledge and Development in Guizhou, China - Ye Tian; Narongruch Woramitmaitree (Journal of Educational Issues, 2024)
The qualitative research methodology was applied in this investigation. The study’s objective was to investigate Yi folk song knowledge and development in Guizhou, China. The contemporary status of the Yi Folk Song is examined. The fieldwork methodology is mostly used for data collection, together with information from the document, using literature and interview methods. Interviews and observation are the primary research tools. To collect study data, we created a questionnaire, an interview, and an observation form based on the research objective. The study results confirmed: There are now around 350 songs recorded in the Guizhou Yi area, with 40 of them being the most popular. A group of 16 people are the inheritors of Yi folk tunes. There are eight recognized inheritors from Guizhou Province and eight recognized inheritors from Guizhou City among them. The number of Yi inheritors in Guizhou is currently small in proportion to the overall Yi population. The decrease in inheritance venues and the use of inheritance venues both have an impact on song inheritance. Yi folk songs have now become the key presentation and inheritance settings for festivals. There are five basic inheritance approaches proposed: 1) Educational institution inheritance 2) Society and community inheritance 3) family inheritance 4) social media inheritance; and 5) socialization and government participation inheritance.